Alexander Scriabin's and Igor Stravinsky's Influence upon Early Twentieth-Century Finnish Music: The Octatonic Collection in the Music of Uuno Klami, Aarre Merikanto and Väinö Raitio - Jurkowski, Edward (Intersections, 2005)
This article examines a significant shift in musical style and compositional technique that occurred in Finland during the 1920s, a time during which the music of Jean Sibelius exerted a strong influence. Specifically, I discuss how the octatonic collection, a prominent feature in the music of the two early twentieth-century Russian modernists Igor Stravinsky and Alexander Scriabin, is incorporated as a fundamental harmonic resource in three celebrated orchestral works: Uuno Klami's 1935 "The Creation of the Earth" (movement one from his five-movement Kalevala Suite), movement one from Aarre Merikanto's 1924 Ten Pieces for Orchestra, and Väinö Raitio's 1921 tone poem Fantasia estatica.